To multiply the polynomials (x + 2) and (x - 4), we use the distributive property.
(x + 2) * (x - 4)
= x * (x - 4) + 2 * (x - 4)
= x^2 - 4x + 2x - 8
= x^2 - 2x - 8
Therefore, (x + 2)(x - 4) is equal to x^2 - 2x - 8.
Multiply the polynomial expression (x+2)(x−4) .(2 points)
3 answers
that is not it:(
Apologies for the incorrect response.
To multiply the polynomial expressions (x + 2) and (x - 4), we can use the FOIL method:
(x + 2)(x - 4)
= x*x + x*(-4) + 2*x + 2*(-4)
= x^2 - 4x + 2x - 8
= x^2 - 2x - 8
Therefore, (x + 2)(x - 4) is equal to x^2 - 2x - 8.
To multiply the polynomial expressions (x + 2) and (x - 4), we can use the FOIL method:
(x + 2)(x - 4)
= x*x + x*(-4) + 2*x + 2*(-4)
= x^2 - 4x + 2x - 8
= x^2 - 2x - 8
Therefore, (x + 2)(x - 4) is equal to x^2 - 2x - 8.